Same-sign multilepton signatures of an SU(2) R quintuplet at the LHC - Sanjib Kumar Agarwalla (Journal of High Energy Physics, 2019)
Abstract We study in detail the collider signatures of an SU(2) R fermionic quintuplet in the framework of left-right symmetric model in the context of the 13 TeV LHC. Apart from giving a viable dark matter candidate (χ 0), this model provides unique collider imprints in the form of same-sign multileptons through the decays of multi-charged components of the quintuplet. In particular, we consider the scenario where the quintuplet carries (B − L) = 4 charge, allowing for the presence of high charge-multiplicity particles with relatively larger mass differences among them compared to (B − L) = 0 or 2. In this paper, we mainly focus on the same-sign n-lepton signatures (nSSL). We show that with an integrated luminosity of 500 fb−1, the mass of the neutral component, M χ 0 $$ M_{χ^0} $$ ≤ 480 (800) GeV can be excluded at 95% CL in the 2SSL (3SSL) channel after imposing several selection criteria. We also show that a 5σ discovery is also achievable if M χ 0 $$ M_{χ^0} $$ ≤ 390 (750) GeV in the 2SSL (3SSL) channel with 1000 fb−1 integrated luminosity.